Neonatal exposure to sevoflurane caused cognitive deficits by dysregulating SK2 channels and GluA2-lacking AMPA receptors in juvenile rat hippocampus. (October 2018) - Yu, Xiangdi; Zhang, Fangxiang; Shi, Jinshan
Abstract: Anesthetics exposure to neonates leads to impairment of hippocampal synaptic plasticity and cognitive functions later in life. This phenomenon complies with the concept of metaplasticity: a priming stimulation can affect induction of synaptic plasticity mins or days later. We aimed to understand whether small conductance Ca 2+ -activated potassium channel type2 (SK2) and subunit composition of AMPA receptors are altered and contribute to sevoflurane-induced metaplasticity. To fulfill this goal, we exposed neonatal rats (postnatal day 7) to 2% sevoflurane for 2 h (sevoflurane rats) and examined synaptic plasticity in the hippocampus and cognitive function in juvenile rats (postnatal day 30–35). We observed that the juvenile sevoflurane rats showed elevation in the threshold for LTP induction, facilitation of LTD induction, and cognitive dysfunctions. Meanwhile, these rats also exhibited increased surface expression of SK2 and enhanced synaptic recruitment of GluA2-lacking AMPA receptors, which possess stronger inward rectification. Blocking SK2 eliminated inward rectification of AMPA receptors in juvenile sevoflurane rats. Interestingly, blocking either SK2 channels or GluA2-lacking AMPA receptors normalized LTP, LTD, and spatial memory in juvenile sevoflurane rats. Our data indicate that neonatal sevoflurane anesthesia have negative impact on cognitive function extended to juvenile rats probably through increasing surface expression of SK2 and synaptic recruitment of GluA2-lacking AMPA receptors. This study provides a new sight for sevoflurane induced metaplasticity. Highlights: Sevoflurane affects LTP, LTD induction and cognitive dysfunctions. Blocking SK2 or GluA2-lacking AMPA receptors reverses sevoflurane's effects. Neonatal sevoflurane anesthesia have negative impact on cognitive function. Such effects are via SK2 channels and GluA2-lacking AMPA receptors.